2016
DOI: 10.1002/btm2.10017
|View full text |Cite
|
Sign up to set email alerts
|

High‐throughput screening of clinically approved drugs that prime polyethylenimine transfection reveals modulation of mitochondria dysfunction response improves gene transfer efficiencies

Abstract: Nonviral gene delivery methods are advantageous over viral vectors in terms of safety, cost, and flexibility in design and application, but suffer from lower gene transfer efficiency. In addition to modifications to nucleic acid design and nonviral carriers, new tools are sought to enhance transfection. Priming is the pharmacological modulation of transfection efficiency and transgene expression, and has demonstrated transfection increase in several compounds, for example, chloroquine and glucocorticoids. To d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 44 publications
0
15
0
Order By: Relevance
“…Our previous work has sought to improve and better understand the biology of nonviral gene delivery by pharmacologically 'priming' cells for increased transgene expression (Nguyen, Beyersdorf, Riethoven, & Pannier, 2016) through modulation of relevant molecular pathways that are important to the biological processes involved in gene delivery (Martin, Plautz, & Pannier, 2015a;Martin, Plautz, & Pannier, 2015b). Specifically, we investigated anti-inflammatory glucocorticoid (Gc) drugs as priming candidates in hMSCs due to reports in other cell types that Gc can increase transfection efficiency by increasing plasmid DNA (pDNA) nuclear internalization or reducing the inflammatory response to transfection (Braun et al, 1999;Kim, Kim, Bae, Choi, & Lee, 2009).…”
mentioning
confidence: 99%
“…Our previous work has sought to improve and better understand the biology of nonviral gene delivery by pharmacologically 'priming' cells for increased transgene expression (Nguyen, Beyersdorf, Riethoven, & Pannier, 2016) through modulation of relevant molecular pathways that are important to the biological processes involved in gene delivery (Martin, Plautz, & Pannier, 2015a;Martin, Plautz, & Pannier, 2015b). Specifically, we investigated anti-inflammatory glucocorticoid (Gc) drugs as priming candidates in hMSCs due to reports in other cell types that Gc can increase transfection efficiency by increasing plasmid DNA (pDNA) nuclear internalization or reducing the inflammatory response to transfection (Braun et al, 1999;Kim, Kim, Bae, Choi, & Lee, 2009).…”
mentioning
confidence: 99%
“…An efficient nonviral gene delivery system for ex vivo genetic modification of clinically relevant hMSCs is lacking, however, our lab has previously demonstrated that pharmacological priming, or the addition of compounds to the culture media to modulate the cellular response to transfection, is a simple and effective method to enhance transfection in multiple cell types [15][16][17][23][24][25][26]. The idea of priming was developed after our studies using microarray analysis of transfected versus treated, but untransfected cells, where differentially expressed endogenous genes were identified between each condition in HEK 293 T cells and the expression of these identified genes were perturbed pharmacologically (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…primed) in order to gain insight into the role of endogenous molecular factors in the transfection process [23][24][25][26]. Furthermore, our lab sought to expand our transfection priming library by screening the National Institutes of Health Clinical Collection (NCC), a collection of over 700 small molecules made available for drug repurposing [21], for compounds that could prime polymer-mediated transfection to HEK 293 T cells [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Angela Pannier and coworkers describe the identification of small molecule drugs that enhanced DNA transfection efficacy using a high throughput screening approach . Stephanie Seidlits, Lonnie Shea, and their colleagues employ gene therapy to reduce neuroinflammation following spinal cord injury .…”
mentioning
confidence: 99%